Hubungan Antara Lokasi Awal Tumor Dengan Tipe Histopatologi Pada Pasien Kanker Payudara di Rumah Sakit Umum Cut Meutia Aceh Utara - Rizka, Adi; Sri Rahayu, Mulyati; Husna Lubis, Rehani (Jurnal Ilmiah Manusia Dan Kesehatan, 2025)
Breast cancer is the abnormal, rapid and uncontrolled growth and development of cells in the breast tissue. The most common symptom is characterized by a lump or thickening in the breast called the initial site of the tumor. This abnormal cell growth can start in the ductal or lobular epithelium of the breast and becomes the histopathologic type of the cancer. The clinicopathological characteristics of breast cancer, including the initial location of the tumor and the histopathological type, are both factors in the prognosis of breast cancer. This study intends to ascertain the correlation between the tumor's original location and the type of breast cancer histopathology in patients with breast cancer at Cut Meutia General Hospital, North Aceh. This type of research is quantitative analytic using crossectional method which was conducted in October 2024 - November 2024. The number of samples was 72 breast cancer patients with purposive sampling technique that met the inclusion and exclusion criteria. The results showed that the initial location of the most tumors was in the upper outer quadrant (51.4%) and the most histopathological type was invasive ductal carcinoma (73.6%). The results of the chi square test showed that the p value <0.05 (p = 0.010). According to the study's findings, patients with breast cancer at Cut Meutia General Hospital North Aceh have a correlation between the kind of histology and the tumor's original location